Problematika Model Electronic Learning Dalam Wabah Coronavirus Disease 2019 Di Madrasah Ibtidaiyah Bahrul Ulum Pelemwatu Menganti Gresik - Cici Mardiana; Mulyadi (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2021)
The outbreak of Coronavirus Disease 2019 which was first detected appeared in China, precisely in Wuhan City, China at the end of 2019. This virus then became a terrible terror for the world community, especially after claiming thousands of human lives in a relatively short time. Based on the decision of the Minister of Education and Culture of the Republic of Indonesia in the context of preventing the spread of Corona Virus Disease, the entire scope of education applies an online/electronic learning model. The electronic learning model is a program for organizing online learning classes to reach a massive and broad target group. Therefore, an obstacle or problem must be solved so that the expected results can be achieved. The problems to be sought through this research are: a) How is the learning process based on electronic learning? b) What are the problems faced in the electronic learning model?, and c) What are the efforts made to overcome the problems of the electronic learning model?. This study uses a qualitative approach, where researchers directly conduct research in the field. The methods used to initiate the data in this study include observation, interviews, and documentation. The results showed that, a) the process of implementing electronic learning conducted by teachers at Madrasah Ibtidaiyah Bahrul Ulum Pelemwatu Menganti Gresik was well structured in accordance with the provisions recommended by the government. b) The problems experienced in the application of the electronic learning model at Madrasah Ibtidaiyah Bahrul Ulum are problems experienced by teachers who cannot supervise learning directly. Lack of understanding of the material presented by the teacher. Related to electronic devices/mobile phones, such as signal constraints on data packages, not all students have electronic devices/mobile phones, and c) Efforts are being made to overcome the problems, namely holding home visits, bringing students/guardians to school for those who do not have mobile phones. Provide wifi for the teacher council for electronic learning learning process activities.